PEDAGOGICAL AND PSYCHOLOGICAL FACTORS OF INTEGRATION TEACHING IN PRIMARY CLASSES - Eshmanova Nodira Nazarqulovna (Web of Journals Publishing, 2023)
In this article discussed that, importance of interdisciplinary integration, some of the requirements and conditions for the introduction of integrated education in the primary grades, and described in detail the general features of the integrated course.
Keywords: integration, interdisciplinary integration, educational effectiveness, primary education, integration lessons, maths.